Urine cyclic nucleotide concentrations in cancer and other conditions; cyclic GMP: a potential marker for cancer treatment. Issue 8 (August 1982) - Turner, G A; Ellis, R D; Guthrie, D; Latner, A L; Monaghan, J M; Ross, W M; Skillen, A W; Wilson, R G
Abstract : Cyclic guanosine 3', 5' monophosphate (cyclic GMP) and cyclic adenosine 3', 5' monophosphate (cyclic AMP) have been determined in random urine specimens from 95 healthy individuals, 60 patients with non-cancerous conditions, 52 patients with benign tumours, and 74 patients with malignant tumours. Concentrations of cyclic GMP have also been determined in a number of other groups, including some undergoing cancer treatment. Ninety-three per cent of cancer patients had raised urinary cyclic GMP concentrations compared to the reference range for healthy subjects. For the non-cancerous and benign groups, 33% and 42% respectively had raised concentrations. The urine cyclic AMP concentrations were similar in all groups. Urine cyclic GMP appeared to rise early in the onset of malignant growth. Successful cancer treatment was accompanied by a dramatic fall in the urine cyclic GMP concentrations, whereas if the treatment was unsuccessful the level did not change. It is concluded that urine cyclic GMP may have important applications in the monitoring of cancer treatment.